The Influence of Organizational Culture and Leadership Style on Employees' Innovative Work Behavior at the South Coast Regional Planning Agency with Innovation Willingness as an Intervening Variable - Efendi, Tifani; Frinaldi, Aldri (SAFE-Network, 2025)
This study examines the influence of organizational culture and leadership style on employees’ innovative work behavior, with innovation willingness serving as a mediating variable, in the South Coast Regional Development Planning, Research, and Innovation Agency (Bappeda Litbang). The research aims to determine the direct and indirect effects of organizational culture and leadership on innovative work behavior and to evaluate the role of innovation willingness as a psychological mediator. A quantitative causal associative approach was employed, with a population of 47 employees included through a census method. Data were collected using a structured questionnaire with a five point Likert scale and analyzed using path analysis in SPSS 25. The results indicate that organizational culture has a significant and positive effect on innovation willingness and innovative work behavior, while leadership style also contributes positively, albeit with a smaller magnitude. Innovation willingness strongly mediates the relationship, amplifying the impact of organizational culture and leadership on innovative behavior. The regression model shows that 53.1% of the variance in innovative work behavior is explained by the three variables. These findings suggest that fostering a supportive organizational culture and effective leadership, combined with enhancing employees’ innovation willingness, is crucial to promote innovative behavior in public institutions. The study provides practical insights for policymakers and administrators seeking to strengthen organizational innovation and develop human resources capable of adapting to dynamic and complex public sector challenges.